Pengembangan Bahan Ajar Digital Articulate Storyline Materi Kerajaan di Nusantara - Fitri Ajeng Galuh; Wahyu Susiloningsih; Rarasaning Satyaningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to develop teaching materials using Articulate storyline 3 media that are valid, practical and effective. The use of technology in today's developments in the world of education is required to be able to develop approaches to learning. by utilizing IT technology which is one of the important factors that might be able to provide faster knowledge transformation for students. The results of the research on the development of the learning media developed obtained a level of validity in the very valid category. The results of the expert response questionnaire showed that the learning media was very practical with the results of the teacher response questionnaire showing a percentage of material practice by material experts of 93.7%. while the results of instrument validation by language experts were 86.1%. The results of media effectiveness show very effective learning outcomes with a percentage of 83.3%. Thus the learning media developed is declared valid, practical, effective and worthy of development.”